Badania biometryczne serca i dużych naczyń tętniczych w rozwoju prenatalnym człowieka - Chrobot, Andrzej; Bożiłow, Władimir; Czerwionka-Szajlarska, Mieczysława; Swincow, Grażyna (Polskie Towarzystwo Antropologiczne, 1996)
The paper contains the results of the investigation of selected dimensions of heart and great vessels. The'studies were carried out on a total of 197 fetuses (98 males and 99 females) in the age from the 3rd to 7th month of perinatal life. The aim of this work was to receive the data on the process of formation of sexual differences in the dimensions of: heart, aorta, pulmonary trunk, aortic arch ramifications, and the course of their growth rate.
Biometrical studies of heart and great arterial vessels in fetal ontogenesis